Model Pembiayaan Pembangunan Transportasi Kereta Api Melalui Skema Public Private Partnership (KPBU) - Haryono, Rakhmat Haryono; Ajibroto, Kunto (Koaliansi : Cooperative Journal, 2024)
This study analyzes the challenges of infrastructure development in regions such as West Papua which have difficult geography and sparse populations, and proposes that land transportation systems, including trains, can improve infrastructure efficiency. The research methods used include economic and financial feasibility analysis, social benefit cost analysis (ABMS), analysis of forms of cooperation in providing infrastructure, as well as analysis of the need for government support and government guarantees. The research results show that the proposed rail fares for the West Papua Railway will generate sufficient revenue to support the project. The study also considered alternative revenue sources from various sources, such as station space rental, parking, and advertising. With the PPP Scheme (PPP) for the railway project, it is hoped that investment can be returned within a reasonable time and support regional economic development. However, government support in the form of VGF will be required to secure this project. This railway project is expected to be a positive contribution to the development of the region's infrastructure and economy